Morphology and bacterial colonisation of tooth/ceramic restoration interface after different cement excess removal techniques - Anami, Lilian Costa [UNESP]; Pereira, Cristiane Aparecida [UNESP]; Guerra, Elen [UNESP]; de Assuncao e Souza, Rodrigo Othavio; Cardoso Jorge, Antonio Olavo [UNESP]; Bottino, Marco Antonio [UNESP] (Elsevier B.V., 2012)
Objectives: To evaluate the influence of different protocols for resin cement removal during cementation on biofilm formation.Methods: Twenty-eight ceramic blocks, which were injected under pressure, were placed over enamel blocks obtained from freshly extracted bovine incisors. The ceramic blocks were cemented to the enamel blocks using a dual-cured resin cement and the excess resin was removed according to the experimental group: TS: Teflon spatula; BR: brush; BR+: brush and polishing; SB+: scalpel blade and polishing. After autoclaving, the samples were colonised by incubation in a sucrose broth suspension standardised with Streptococcus mutans in microaerophilic stove. Specimens were quantitatively analysed for bacterial adherence at the adhesive interface using confocal laser scanning microscopy and counting the colony forming units, and qualitatively analysed using SEM. The roughness (Ra/Rz/RSm) was also analysed. Data were analysed by 1-way ANOVA and Tukey's test (5%).Results: The roughness values ranged from 0.96 to 1.69 mu m for Ra (p > 0.05), from 11.59 to 22.80 mu m for Rz (p = 0.02 < 0.05) and from 293.2 to 534.3 mu m for RSm (p = 0.00). Bacterial adhesion varied between 1,974,000 and 2,814,000 CFU/ml (p = 0.00). Biofilm mean thickness ranged from 0.477 and 0.556 mu m (p > 0.05), whilst the biovolume values were between 0.388 and 0.547 mu m(3)/mu m(2) (p = 0.04). Lower values for roughness, bacterial adhesion, biofilm thickness and biovolume were found with BR, whilst TS presented the highest values for most of the parameters. SEM images confirmed the quantitative values.Conclusions: The restoration margin morphology and interface roughness affects bacterial accumulation. The brush technique promoted less bacterial colonisation at the adhesive interface than did the other removal methods.Clinical significance: The brush technique seems to be a good option for removing the excess resin cement after adhesive cementation in clinical practice, as indicated by its better results with lower bacterial colonisation. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Bacterial colonisation; Removal techniques; Restoration margin; Roughness; Tooth; Ceramic